Regulating CEO Pay: Evidence from the Nonprofit Revitalization Act - Babenko, Ilona; Bennett, Benjamin; Sen, Rik (Review of Financial Studies, 2026)
Abstract This paper examines CEO pay at nonprofits. Using compensation data for 14,111 nonprofits, we find that CEO pay dropped by 2% after legislation in New York reduced CEOs’ ability to influence their own pay. Despite lower pay, CEOs exerted more effort, and nonprofit performance improved. The effects were stronger at commercial nonprofits than at charities and for male CEOs than female CEOs. These findings are consistent with a model where some nonprofit CEOs derive meaning from their work and compensation can be rigged. Overall, our results suggest that regulation that targets the pay-setting process can improve organizational outcomes at nonprofits.